Chronic Hyperkeratotic Hand Dermatitis - Hillary Clarence Danduru Rante Tondok (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Hyperkeratotic hand dermatitis (HHD) is a chronic hand eczema subtype marked by thick hyperkeratotic plaques, painful fissures, and minimal erythema or vesiculation.It is diagnostically challenging due to overlap with palmoplantar psoriasis and keratoderma and is strongly linked to repeated irritant exposure in wet work. A 60-year-old male taro leaf farmer presented with itching and burning on the palms and backs of both hands, spreading to the forearms for 2–3 weeks. Examination revealed papules, hyperpigmented plaques, erythematous macules, irregular scaling, and about 1 cm palmar fissures on both hands. The working diagnosis was chronic hyperkeratotic hand dermatitis. Initial treatment included oral cetirizine, topical betamethasone valerate, and Vaseline gel, plus education on using long rubber gloves at work. HHD results from skin barrier dysfunction and keratinocyte hyperproliferation caused by repeated irritant exposure. In this case, exposure to taro leaves and prolonged rubber glove use likely maintained irritation and occlusion. Differential diagnoses include palmoplantar psoriasis, contact dermatitis, and tinea manuum. Management involves potent corticosteroids, antihistamines, occlusive emollients, and occupational modifications such as replacing gloves and limiting occlusion time. Identifying occupational factors in HHD is essential. Effective management requires combined topical therapy, symptom control, and strict workplace modifications, along with patient education and allergy screening if needed.